Mulheres indígenas em rede: sociobiodiversidade do local para o global? - BATISTA, Mariluz Coelho (Universidade Federal do Pará, 2023)
The involvement of indigenous peoples in cyberspace has grown since 2020, particularly during the Covid-19 pandemic. In this regard, indigenous women have taken on a leading role in virtual networks to advocate for the rights of indigenous peoples. This research aims to explore whether this appropriation of technology and cyberspace by indigenous peoples can serve as a means to protect both the tangible and intangible heritage of the Amazon, with a focus on the significant contribution of indigenous women. The study examines the presence of indigenous women in networked activities, exploring the concept of "place politics" and the shift from the local to the global. The research period spans from May 2020 to January 2022, utilizing a qualitative methodology that includes integrative bibliographic research, exploratory document analysis, and observations employing a multi-situated ethnographic approach on the Twitter platform. Through its findings, this research seeks to contribute to the development of public policies aimed at safeguarding the socio-biodiversity of the Amazon, with indigenous peoples, particularly indigenous women, as key actors in virtual networks. The ultimate goal is to identify actions and strategies by showcasing the political agency of these individuals on online platforms, in order to protect the Amazon biome and the intangible and material heritage of Indigenous Peoples, thereby mitigating climate risks and preserving socio-biodiversity.